The Association between Dystemperament and Prevention of Diseases: A Systematic Review - Kopaei, Rafieian (J Clin Diagn Res, 2016)
INTRODUCTION: Temperament or mizaj is referred to four different humors differentiating individuals and as a result, proposing different preventive measures for their diseases. AIM: In this study, a systematic and purposeful review with emphasis on the research question was done to retrieve, evaluate and consolidate the required information. MATERIALS AND METHODS: Computerized search of published original articles with fulltext was performed using PubMed and Web of Science, Medline data Science direct, ProQuest, SID and Cochrane Library bases as well as local references from March 1990 to March 2016. The key terms used were “temperament”, “Dystemperament”, “prevention”, “health promotion”, “sue mizaj”, “treatments” and “preventive measures”,”preventive medicine”. Original and translated books were also used. Out of 25 articles, 9 were selected. RESULTS: The findings of this study indicated that there are six essential factors (asbab-e-sitlah Zarooriya), in preventing diseases which includes air, water, food, rest and improvement of body, soul and mind, sleeping and awakening, retention and discharge of fluids, solids, gases and energy from the body and based on the aforementioned causes, some Tadbeer were introduced as Tadabir-i-Nafas (air), Tadbeer-bil-food, Tadbeer-bil-drinks, Tadbeer bil-exercise and physical relaxation, Tadbeer-bil-sleep and wakefulness, Tadbeer bil-retention and discharge. CONCLUSION: There are two differences between these two kinds of medicine; firstly, although some preventive factors are overlapped in traditional and mainstream medicines (including nutrition (both food and drink), physical activity and sleep), some of the traditional preventive factors become undelined (retention, air) and some new preventive factors get highlighted in mainstream medicine (e.g., not smoking, not having stress, …); secondly, rules of preventive medicine in Unani system were mentioned in detail and were different for different people with different types of temperament, while the mainstream medicine states its rules, generally for different types of people.